O contrato de opção de compra nas sociedades limitadas: incentivo à inovação e alocação de mão de obra qualificada - Jesse Barbosa Antunes de Morais (2016)
The study presented here aims to investigate - from the Law 10,402 / 2002 (Civil Code), Law 6.404 / 1976 (Law Corporation) and the Constitution of the Federative Republic of Brazil - the possibility of institution by limited companies stock option plans for employees (employee stock option plan), as an incentive to innovation and labor allocation of skilled labor. The central idea is that the innovative firm - despite and because of scarcity of resources - be legally able to give itself (its capital) to its employees in order to increase their absorption capacity and, consequently, generate innovation and development. To confirm or refute the hypothesis proposed, analyzed the regulation of the purchase option Institute of Law of Corporations and the form of business organization of limited partnerships provided for in the Civil Code, as well as their inter-faces within Constitutional Law, Business, Labor, Social Security, Administrative and Economic. The research was exploratory, descriptive and explanatory, based on legislation, doctrine and jurisprudence. Two theoretical and methodological aspects guided the work. First, the "social-scientific" aspect - anointed the "transformation of legal thinking in technology," notably to provide economical alternative and socially useful hand allocation of skilled labor for innovative firms organized as limited partnerships. Second, the legal-dogmatic side, who studied the subject from a strictly normative approach - that is: played the Brazilian legal system to determine the consequences and competitive advantages in the use of buying corporate shares option plan for employees of innovative firms, organized as limited partnerships. In conclusion, the hypothesis is verified. Extract also the of Brazilian legal system not only the legality in the management of the Institute for limited liability companies, but its constitutional incentive.